Analisis Kesulitan siswa kelas II A dalam menyelesaikan Soal Cerita Matematika di SDI Asy-Syuhada Pamekasan Madura - Bukhori, Imam; Aluf, Wilda Al; sakir, Abdus (Mafa Press in Collaboration with PGMI Tarbiyah Faculty IPMAFA, 2025)
The ability to solve mathematical word problems is an essential skill for elementary school students, especially lower grades. However, second-grade students at SDI Asy-Syuhada Pamekasan still face various difficulties in understanding problem content, determining arithmetic operations, and overcoming anxiety when faced with long or complex problems. This study aims to analyze the difficulties faced by second-grade students in solving mathematical word problems, along with the contributing factors and teachers' strategies for addressing them. The study used a descriptive qualitative approach, with data collection techniques including observation, interviews, tests, and documentation. Data were analyzed using the Miles and Huberman model through the stages of data reduction, data presentation, and conclusion drawing.The results showed that the students' primary difficulties lie in understanding the problem content, selecting arithmetic operations, and a lack of accuracy. Contributing factors include weak reading comprehension skills, poor mastery of basic mathematical concepts, the use of problem language that is inappropriate for the students' developmental level, and a lack of interactive learning media. Furthermore, affective factors such as fear and low self-confidence exacerbate the situation. Teachers have implemented learning strategies such as a contextual approach, gradual practice, and individual guidance, but the results have not been optimal. Therefore, learning innovations are needed through varied and enjoyable methods, such as educational games, visual media, and contextual approaches relevant to everyday life to increase students' motivation, understanding, and confidence in solving math story problems.Keywords: learning difficulties, math story problems, second-grade students